Analysis of the Influence of Trust, Security and E-Service on Purchasing Decisions for Climbing Tickets Through The Tiket Pendakian Application - Bekti Widodo, Wahyu; Pakaja, Fachrudin (International Journal of Economics and Business Management, 2025)
The advancement of digital technology has significantly changed tourism services, including the mountain climbing ticket booking system. One such innovation is the Tiket Pendakian application, an Indonesian platform designed to facilitate online reservations for mountain climbing activities. This study aims to examine the influence of trust, security, and e-service quality on users' decisions to purchase climbing tickets through the application. A quantitative research method was used, using a survey distributed to 100 respondents who had used the platform. Data were collected through an online questionnaire and analyzed using multiple linear regression to assess the partial and simultaneous effects of these variables. The results showed that trust and e-service quality had a positive and significant influence on purchasing decisions. In contrast, security did not show a significant partial effect, although the three variables collectively influenced purchasing decisions. These findings underscore the importance of building user trust and providing high-quality digital services to promote the continued use of online booking platforms. This study offers strategic insights for application developers and contributes to academic discussions on digital tourism and information systems. These results are also in line with prior findings (Flavián et al., 2006), (Urban et al., 2000), (Cyr, 2008), (Lin, 2007).